Valuation Model For The Merger & Acquisition Of PT Bank Pembangunan Daerah Banten Tbk (BEKS) - Raden Maart Adi Waskita Tjahjono; Isfan Ferli; Jerry Heikal (Journal Informatic, Education and Management (JIEM), 2025)
Merger and acquisition of a banking company are generally understood as efforts to improve the company by combining strengths or balancing the weaknesses of one company with the strengths of another. To face the dynamics of the domestic and global economy and information technology, it is necessary to strengthen the structure, resilience, and competitiveness of the national banking industry, which can be achieved by strengthening bank capital and banking consolidation in Indonesia, especially Regional Development Banks. To encourage the stability of the banking industry, particularly the strengthening of individual banks, the merger and acquisition strategy in the form of banking consolidation needs to be considered. Banking consolidation policy is one of the policy options taken by regulators to strengthen the stability of the financial system. This study aims to determine the appropriate transaction structure and price for PT Bank Pembangunan Daerah Banten Tbk (BEKS). This research uses quantitative and descriptive analysis of the financials of PT Bank Pembangunan Daerah Banten Tbk (BEKS) using the Free Cash Flow to the Firm (FCFF), Liquidation and Accounting Valuation, and Relative Valuation methods. The results project significant growth for the company over five years. The equity value per share of BEKS is Rp 14,89 compared to the market share price of Rp 23, indicating overvaluation. The acquiring company needs to carefully reconsider BEKS prospects and negotiate the price before proceeding with the acquisition process.